On the existence of a periodic solution of the Liénard system - IGNATYEV, Alexander (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The Li'enard system dxdt=y,dydt=-f(x)y-g(x) is considered. Under some assumptions on functions f(x) and g(x), we estimate the domain of location of the unique stable limit cycle of the Li'enard system.This estimation has the form α_2<x<α_1, where α_1 and α_2 are respectively the positive the negative roots of the equation _0^α[_0^xf(s)ds] g(x)dx=0. Mathematics Subject Classification (2010): 34C05, 34C07, 34C25, 34C15, 34A26.